Cue Card Media in Reducing The Students Speaking Anxiety - Nurteteng Nurteteng (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
The objective of this research is to find out whether a cue card media impact or not reducing speaking anxiety at grade in MTs Az-Zikra Kota Sorong. Related to the objective of the researcher used pre-experimental quantitative research design. The design of this research is one group pretest posttest. The population of this research was eighth grade students of MTs Az-Zikra Kota Sorong with the sample is 34 students. In the collecting the data, the researcher used anxiety questionnaire which consist of 32 items, and it was applied in pretest and posttest. In analyzed the data, the researcher used SPSS 20 program to calculate the data. The result finding of the research showed that, there is a difference score between the result of the anxiety questionnaire in pretest and posttest. It can be seen from the questionnaire result in pretest was 76,4 % categorized into severe anxiety level reduced become 53,6% in posttest. It can be concluded that cue card media can reduce the speaking anxiety of the students.